Seasonality of abundance, reproduction and epiphytism in Gracilaria cliftonii Withell, Millar & Kraft, 1994 from Western Australia - Muñoz Serrato, Julieta Margarita (Curtin University, 2010)
The Government of Western Australia (RIDC) has identified seaweed cultivation as an alternative activity to utilise inland saline water bodies in rural areas. Gracilaria cliftonii has been identified as a potential species for inland saline water aquaculture and is high agar yield (62%). However, information related to its seasonal variations from natural populations has not yet been reported. The aim of the present research was to determine the seasonality in biomass, abundance, epiphytism and chemical properties of Gracilaria cliftonii collected from the wild. G. cliftonii samples were collected during 6 seasons from Autumn 2008 to Winter 2009 from Point Peron, Western Australia. Maximum biomass of G. cliftonii was observed in Winter (42.2 g m[superscript]2) while maximum total abundance occurred in Summer (3.4 nh/m[superscript]2). Three reproductive stages viz. tetrasporophyte, carposporophyte and male gametophyte were observed all year round.The biomass and abundance of tetrasporophyte and carposporophyte stages from G. cliftonii in Autumn 2008 were significantly higher than other seasons while the biomass of the vegetative stage was significantly higher in Spring and Summer. Abundance showed a strong correlation (R[superscript]2=0.96; p<0.05) with day length. Over the study period, tetrasporophyte and carposporophyte were significantly longer (p<0.05) than male gametophyte and vegetative stages.Epiphytism was a common phenomena observed in G. cliftonii. Epiphytic biomass was significantly higher in Autumn and Winter 2008, while, epiphytic load was significantly higher in Spring 2008. Over entire study period twenty four macroalgae epiphytes were recorded, with the Ceramiales as the most dominant group and Hypnea episcopalis and Polysiphonia forfex the most dominant epiphytes. The epiphytes of G. cliftonii are attached in different ways to its thallus. Although, most of the epiphytes were attached superficially to the surface, Polysiphonia sp., and Ceramium sp. were penetrated into the host tissue.The chemical composition of G. cliftonii varied among life stages and seasons and consisted mainly of carbohydrates followed by ash and protein. The physicochemical properties of G. cliftonii were mainly influenced by seasons and all the values obtained were higher than previous recorded for other macroalgae. Finally, yield and properties of the agar of G. cliftonii were also demonstrated to be influenced by seasons and life stages.The present study shows that biomass of G. cliftonii, epiphytism, and chemical compositions are highly variable and are result of the effect of seasons and life stages. Therefore, the effects of seasons and life stages have to be considered for culture and exploitation of the species.